2017
DOI: 10.1128/aem.00503-17
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of High Pressure on Bacillus licheniformis Spore Germination and Inactivation

Abstract: Bacillus and Clostridium species form spores, which pose a challenge to the food industry due to their ubiquitous nature and extreme resistance. Pressurization at Ͻ300 MPa triggers spore germination by activating germination receptors (GRs), while pressurization at Ͼ300 MPa likely triggers germination by opening dipicolinic acid (DPA) channels present in the inner membrane of the spores. In this work, we expose spores of Bacillus licheniformis, a species associated with food spoilage and occasionally with food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…FCM has thus been used increasingly for studying spore germination in general. However, only very few studies used FCM to study spore germination under HP (Black et al, 2005;Mathys et al, 2007;Baier et al, 2011;Reineke et al, 2013a;Borch-Pedersen et al, 2017).…”
Section: Methods To Study Heterogeneous Spore Germinationmentioning
confidence: 99%
See 3 more Smart Citations
“…FCM has thus been used increasingly for studying spore germination in general. However, only very few studies used FCM to study spore germination under HP (Black et al, 2005;Mathys et al, 2007;Baier et al, 2011;Reineke et al, 2013a;Borch-Pedersen et al, 2017).…”
Section: Methods To Study Heterogeneous Spore Germinationmentioning
confidence: 99%
“…Previous studies on HP-treated Bacillus spores reported the usage of nucleic acid binding stains including the membrane-permeable and -impermeable stains SYTO16 and propidium iodide (PI), respectively, to distinguish between dormant, germinated and potentially inactivated spores (Black et al, 2005(Black et al, , 2007Mathys et al, 2007;Reineke et al, 2013a;Borch-Pedersen et al, 2017). The underlying assumption here is that dormant spores should not or only very poorly be stained by either SYTO16 or PI.…”
Section: Current State and Challenges Of Using Flow Cytometry To Studmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, it is important to note that HS-RT can reduce not only the load of vegetative cells as conventional pasteurization does, but can also decrease the endospore load. Many papers in the literature have shown that relatively low pressures induce endospore germination [35][36][37][38]. Thus, during HS-RT, pressure can produce the germination of endospores, and at appropriate pressure levels, their subsequent outgrowth is not fulfilled.…”
Section: Microbial Loadmentioning
confidence: 99%